2022
DOI: 10.1002/slct.202103821
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of a Single‐Stranded DNA Aptamer Modified Near‐infrared, Water‐Soluble Fluorophore for Lung Cancer Cell Imaging

Abstract: In recent years, aza‐boron dipyrromethene (aza‐BODIPY) derivatives have attracted considerable attention as fluorescent imaging agents. In this work, two polyethylene glycol functionalized water soluble aza‐BODIPY derivatives (a mono cycloaddition product 1PEG‐BOD and a double cycloaddition product 2PEG‐BOD) were synthesized through a cycloaddition click reaction between aza‐BODIPY and N3‐PEG2000‐COOH. The absorption and fluorescence profiles of these two compounds were in near‐infrared region. The fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Previous studies on aza-BODIPY conjugated with poly(ethylene glycol) (PEG-BODs) reported the ϕ F to be 0.008–0.07 in methanol. 77 ϕ F values of the PBAEs in an aqueous solution ranged between 0.0034 and 0.0255 with respect to the reference PS ( ϕ F of MB: 0.22). Although the values were relatively low, the polymers displayed strong radiation in the NIR region in cell culture experiments.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies on aza-BODIPY conjugated with poly(ethylene glycol) (PEG-BODs) reported the ϕ F to be 0.008–0.07 in methanol. 77 ϕ F values of the PBAEs in an aqueous solution ranged between 0.0034 and 0.0255 with respect to the reference PS ( ϕ F of MB: 0.22). Although the values were relatively low, the polymers displayed strong radiation in the NIR region in cell culture experiments.…”
Section: Resultsmentioning
confidence: 97%